Paramedian forehead flap combined with hinge flap for nasal tip reconstruction - Felipe Bochnia Cerci; Gerson Dellatorre (Sociedade Brasileira de Dermatologia, 2016)
Abstract The paramedian forehead flap is a great option for restoration of complex nasal defects. For full-thickness defects, it may be used alone or in combination with other methods. We present a patient with a basal cell carcinoma on the distal nose treated by Mohs micrographic surgery, and a resulting full-thickness defect repaired with paramedian forehead flap combined with a hinge flap. For optimal results with the paramedian forehead flap, adequate surgical planning, patient orientation and meticulous surgical technique are imperative.